PELATIHAN PEMBUATAN DIMSUM AYAM BAGI IBU RUMAH TANGGA DI DESA KALEBAJENG KECAMATAN BAJENG KABUPATEN GOWA - Latang, Latang; Arsyad, Yolandika; Rahmawati, Rahmawati; Alamsyah, Muhammad Nur; Zahra, Shofyatun (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
Community empowerment through the development of the creative economy is an important strategy to improve welfare based on local potential. The community of Kalebajeng Village, Bajeng District, Gowa Regency has considerable potential to develop culinary businesses; however, their skills in processing food products with economic value remain limited. This condition necessitates a training program that can enhance the community’s practical skills. This service activity aims to provide practical knowledge and skills while encouraging housewives in Kalebajeng Village to utilize business opportunities through culinary products, particularly chicken dim sum. The method employed was participatory training using presentation, demonstration, and hands-on practice techniques. Program evaluation was carried out through participation evaluation, which assessed the level of involvement and activeness of participants in discussions and practice, and skill evaluation, which used observation sheets and assessment rubrics to measure participants’ abilities in processing and serving dim sum products. The results showed that approximately 80% of participants experienced an increase in technical skills in processing, packaging, and storing chicken dim sum, along with improved knowledge of offline and digital marketing strategies. The implication of this activity is the emergence of opportunities for the development of micro, small, and medium enterprises (MSMEs) in the culinary sector, which can contribute to increasing household income and strengthening the village economy. Therefore, this training can serve as an effective medium for creative economic empowerment and may be replicated in other regions according to their respective culinary potentials.